Ethnic reasoning in social identity of Hebrews: A social-scientific study - Kissi, Seth (HTS teologiese studies, 2017)
Ethnicity reasoning offers one way of looking at social identity in the letter to the Hebrews. The context of socio-economic abuse and hardships of the audience creates a situation in which ethnicity in social identity becomes an important issue for the author of Hebrews to address. This article is a social-scientific study which explores how the author establishes the ethnic identity of the audience as people of God. While this ethnic identity indicates the more privileged position the readers occupy in relation to the benefits of God accessible to them, it also provides the author with the appropriate social institutions and scripts by which his demand for appropriate response to God and the Christian group becomes appreciable and compelling. The article involves the definition of social-scientific criticism, ethnicity and social identity, and discusses the social context of the letter to the Hebrews. It then explains how some social scripts within specific ethnic institutions give meaning to the demands the author makes from his readers.